1999
DOI: 10.1074/jbc.274.5.2893
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Extracellular Signal-regulated Kinase (ERK) Docking Site in Ribosomal S6 Kinase, a Sequence Critical for Activation by ERK in Vivo

Abstract: Glutathione S-transferase (GST)-fusion proteins containing the carboxyl-terminal tails of three p90 ribosomal S6 kinase (RSK) isozymes (RSK1, RSK2, and RSK3) interacted with extracellular signal-regulated kinase (ERK) but not c-Jun-NH 2 -kinase (JNK) or p38 mitogenactivated protein kinase (MAPK). Within the carboxylterminal residues of the RSK isozymes is a region of high conservation corresponding to residues 722 LAQRRVR-KLPSTTL 735 in RSK1. Truncation of the carboxyl-terminal 9 residues, 727 VRKLPSTTL 735 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
241
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(252 citation statements)
references
References 33 publications
9
241
0
2
Order By: Relevance
“…Consequently, we further investigated the effect of THC on the upstream and downstream events that modulate the ERK module of MAPK. The pronounced down-regulation of phospho-Raf-1 was also associated with a marked reduction in phosphorylation of MEK, a major Raf-1 substrate (23), phospho-ERK, the primary MEK target (24), and RSK, the first substrate of ERK (25). This process occurred early, was dependent on cannabinoid receptor ligation, and proceeded upstream of caspase activation.…”
Section: Discussionmentioning
confidence: 92%
“…Consequently, we further investigated the effect of THC on the upstream and downstream events that modulate the ERK module of MAPK. The pronounced down-regulation of phospho-Raf-1 was also associated with a marked reduction in phosphorylation of MEK, a major Raf-1 substrate (23), phospho-ERK, the primary MEK target (24), and RSK, the first substrate of ERK (25). This process occurred early, was dependent on cannabinoid receptor ligation, and proceeded upstream of caspase activation.…”
Section: Discussionmentioning
confidence: 92%
“…The generic MAPK binding site, KIM (kinase interaction motif), is usually rather remote from the phosphorylation site. KIMs come in different variations that can interact with any of the three MAPKs or only a subset [151,153,154]. A meticulous mutational dissection of the KIM in the transcription factor Elk has unveiled subtle differences between ERK and JNK binding to the KIM, and shown that p38 does not require the KIM at all to phosphorylate Elk [155].…”
Section: Picking Activators and Substrates : Erk Docking Sitesmentioning
confidence: 99%
“…17 These latter kinases have 2 catalytic domains, 18,19 and simultaneous mutation of both adenosine triphosphate (ATP) binding sites abrogates kinase activity 20 and results in a dominant-negative mutant. Full catalytic activity of Rsks requires activation by both extracellular signal-regulated kinase (ERK) 21,22 and PDK1 (3-phosphoinositide-dependent protein kinase 1). 23,24 Rsk family kinases have multiple cellular functions.…”
Section: Introductionmentioning
confidence: 99%